Betaine Aldehyde Dehydrogenase (BADH) vs. Flavodoxin (Fld): Two Important Genes for Enhancing Plants Stress Tolerance and Productivity - Niazian, Mohsen; Sadat-Noori, Seyed Ahmad; Tohidfar, Masoud; Mortazavian, Seyed Mohammad Mahdi; Sabbatini, Paolo (Frontiers in Plant Science, 2021)
Abiotic stresses, mainly salinity and drought, are the most important environmental threats that constrain worldwide food security by hampering plant growth and productivity. Plants cope with the adverse effects of these stresses by implementing a series of morpho-physio-biochemical adaptation mechanisms. Accumulating effective osmo-protectants, such as proline and glycine betaine (GB), is one of the important plant stress tolerance strategies. These osmolytes can trigger plant stress tolerance mechanisms, which include stress signal transduction, activating resistance genes, increasing levels of enzymatic and non-enzymatic antioxidants, protecting cell osmotic pressure, enhancing cell membrane integrity, as well as protecting their photosynthetic apparatus, especially the photosystem II (PSII) complex. Genetic engineering, as one of the most important plant biotechnology methods, helps to expedite the development of stress-tolerant plants by introducing the key tolerance genes involved in the biosynthetic pathways of osmolytes into plants. Betaine aldehyde dehydrogenase (BADH) is one of the important genes involved in the biosynthetic pathway of GB, and its introduction has led to an increased tolerance to a variety of abiotic stresses in different plant species. Replacing down-regulated ferredoxin at the acceptor side of photosystem I (PSI) with its isofunctional counterpart electron carrier (flavodoxin) is another applicable strategy to strengthen the photosynthetic apparatus of plants under stressful conditions. Heterologous expression of microbially-sourced flavodoxin (Fld) in higher plants compensates for the deficiency of ferredoxin expression and enhances their stress tolerance. BADH and Fld are multifunctional transgenes that increase the stress tolerance of different plant species and maintain their production under stressful situations by protecting and enhancing their photosynthetic apparatus. In addition to increasing stress tolerance, both BADH and Fld genes can improve the productivity, symbiotic performance, and longevity of plants. Because of the multigenic and complex nature of abiotic stresses, the concomitant delivery of BADH and Fld transgenes can lead to more satisfying results in desired plants, as these two genes enhance plant stress tolerance through different mechanisms, and their cumulative effect can be much more beneficial than their individual ones. The importance of BADH and Fld genes in enhancing plant productivity under stress conditions has been discussed in detail in the present review.